Karakteristik Kepemimpinan Pentakostal-Karismatik: Refleksi Daniel 6:4 - Phanny Tandy Kakauhe; Fransiskus Irwan Widjaja (Sekolah Tinggi Teologi Real Batam, 2020)
Pentecostal-Charismatic Leadership has often drawn criticism from controversy, and many have negative nuances. However, this leadership has dynamic strength which its character, and it must be realized by many parties. The purpose of the discussion in this article is to show the characteristics of Pentecostal-Charismatic leadership through the modeling shown by Daniel. With a qualitative approach and using a descriptive interpretive analysis method in the passage of Daniel 6: 4, the result is that Daniel's charismatic leadership is indicated by the phrase